The Relationship between Physical Self-Concept and Student Self-Confidence - Suci Mutia Lukman; Herman Nirwana (Jurnal Neo Konseling, 2020)
This research is motivated by the low self-confidence of middle school students. Self-confidence is a positive attitude of individuals to develop positive assessments, both towards themselves and the environment / situation being faced. One of the factors suspected to affect the sel confidanace is physical Self-concept. This study aims to (1) describe student confidence, (2) describe students' physical self-concepts, and (3) test whether there is a significant positive relationship between physical self-concept and student self-confidence. This research uses quantitative methods with correlational descriptive analysis. The study population is 313 students Junior High School  2 Ampek Angkek registered in July-December  of periode  academic 2019/2020 and a sample of 174 students were selected by stratified random sampling.The instrument used was a questionnaire. Data were analyzed using descriptive formulas and product moment correlation formulas. The research findings reveal that (1) students' self-confidence is generally in the high enough category, (2) students' physical self-concept is generally in the good category, and (3) significant positive relationship between physical self-concept and students' self-confidence with coefficients correlation of 0.431 and a significance level of 0.000.